1985
DOI: 10.1577/1548-8659(1985)5<330:roeeor>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Review of Ecological Effects of Rapidly Varying Flows Downstream from Hydroelectric Facilities

Abstract: Rapid changes in flow below hydroelectric facilities result from peaking operations, where water is typically stored in a reservoir at night and released through turbines to satisfy increased electrical demand during the day. Potential impacts of these short‐term, recurring disturbances of aquatic systems below dams are important considerations in hydropower development. Reduced biotic productivity in tailwaters may be due directly to flow variations or indirectly to a variety of factors related to flow variat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
234
0
5

Year Published

1994
1994
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 316 publications
(246 citation statements)
references
References 0 publications
3
234
0
5
Order By: Relevance
“…Literature reviews on the effects of hydropeaking (e.g. Baumann and Klaus 2003;Cushman 1985;Pellaud 2007) report the stranding of macroinvertebrates due to rapid ramping and the increase in catastrophic drift (e.g. Céréghino and Lavandier 1998;Céréghino et al 2002) during sudden increases in discharge, water levels and flow velocities.…”
Section: Problematic Nature Of Hydropeakingmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature reviews on the effects of hydropeaking (e.g. Baumann and Klaus 2003;Cushman 1985;Pellaud 2007) report the stranding of macroinvertebrates due to rapid ramping and the increase in catastrophic drift (e.g. Céréghino and Lavandier 1998;Céréghino et al 2002) during sudden increases in discharge, water levels and flow velocities.…”
Section: Problematic Nature Of Hydropeakingmentioning
confidence: 99%
“…Juvenile fish are further endangered by drift and stranding in off-channel areas and exposed depositional features during water-level decreases (e.g. Baumann and Klaus 2003;Cushman 1985;Saltveit et al 2001). Stranding experiments with juvenile brown trout by Halleraker et al (2003) revealed a relationship between stranding and habitat quality, fish size, season, and ramping rates, as well as habituation to repeated dewatering.…”
Section: Problematic Nature Of Hydropeakingmentioning
confidence: 99%
“…Par rapport à la dynamique de l'habitat, les résultats sur la ouananiche montrent, qu'en moyenne, la mobilité des habitats les plus favorables pourrait augmenter d'un facteur d'environ 15 fois par rapport aux conditions naturelles. Il est cependant très difficile d'établir a priori de quelle façon, et avec quelle intensité une telle variation pourrait affecter les populations naturelles parce qu'il n'existe presque pas d'informations disponibles à ce sujet concernant le saumon atlantique (CUSHMAN, 1985). On peut cependant avancer un certain nombre d'hypothèses.…”
Section: ) En Considérant La Valeur Minimale D'aires Pondérées Utileunclassified
“…On peut cependant avancer un certain nombre d'hypothèses. Les effets négatifs des opérations de pointe sur les ouananiches juvéniles peuvent être classifiés en cinq catégories principales : 1) diminution de la surface disponible pour l'établissement de territoires ; 2) diminution de la disponibilité de nourriture (benthos et dérive d'invertébrés) (CUSHMAN, 1985 ;FISHER et LAVOY, 1972) ; 3) augmentation des dépenses énergétiques pour contrer les forts courants, chercher des abris et/ou établir des nouveaux territoires ; 4) diminution du temps alloué à la quête de nourriture ; 5) augmentation de la mortalité par échouage sur les berges asséchées et par l'entraînement vers l'aval dû aux conditions hydrodynamiques au front de l'onde de lâcher d'eau (CUSHMAN, 1985).…”
Section: ) En Considérant La Valeur Minimale D'aires Pondérées Utileunclassified
See 1 more Smart Citation